Serum Allergen-Specific IgE among Pediatric Patients with Primary Immunodeficiency - Karolina Pieniawska-Śmiech; Aleksandra Lewandowicz-Uszyńska; Magdalena Zemelka-Wiacek; Marek Jutel (MDPI AG, 2022)
Background: Allergy is a clinical condition that reflects a deviated function of the immune system. The purpose of this study was to evaluate serum allergen-specific IgE (sIgE) along with clinical manifestations of allergy in patients with diagnosed primary immunodeficiency (PID). Methods: 72 patients, aged 1-17 years, diagnosed with PID and hospitalized between July 2020 and February 2021 were included in the study. Blood samples were obtained by venipuncture. sIgE (30 allergens), blood eosinophil count, as well as total IgE and IgG were measured and assessed in relation to a detailed medical examination. Results: Serum sIgE was detected in the blood of 50% of the patients in the study group, which significantly correlated (p < 0.0001) with clinical symptoms of allergy. During the period of the study, 61.1% of the patients showed symptoms of allergy, with 77.27% of them having tested positive for sIgE. The total IgE level was elevated in 18.06% of the patients and correlated with clinical symptoms of allergy (p = 0.004). An elevated total IgE level was not observed in children receiving immunoglobulin replacement therapy. Conclusion: The study showed that serum sIgE and total IgE together might be a plausible diagnostic tool for PID patients. However, for patients receiving immunoglobulin replacement therapy, the assessment of total IgE is not useful.